Respuesta :
Answer:
x = 7
Subtract 9 from both sides of the equation. Your equation should then look like 63 = 9x. Next, divide both sides by 9 to get the variable by itself. 63 divided by 9 is 7. Therefore, x = 7.
Answer:
x=7
Step-by-step explanation:
Simplifying
9x + 9 = 72
Reorder the terms:
9 + 9x = 72
Solving
9 + 9x = 72
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + 9x = 72 + -9
Combine like terms: 9 + -9 = 0
0 + 9x = 72 + -9
9x = 72 + -9
Combine like terms: 72 + -9 = 63
9x = 63
Divide each side by '9'.
x = 7
Simplifying
x = 7
hope this helps :D